Efficiency enhancement of TiO2 (active material) solar cell by inserting copper particles grown with pulse voltage electroplating method. (January 2017) - Rokhmat, Mamat; Sutisna; Wibowo, Edy; Khairurrijal; Abdullah, Mikrajuddin
Abstract: Here, we report the manufacture of a solar cell using TiO2 nanoparticles as photon absorbers and copper bridges inserted between the TiO2 particles. The copper bridges were synthesized by the pulse voltage electroplating method, and the effect of the pulse duty cycle was explored. The amount of copper deposited between TiO2 particles can be controlled by varying the duty cycles and the deposition time. We found that the cell fabricated by the deposition of copper at duty cycles of 60% and a deposition time of 30 s exhibited the highest efficiency (2.21%). Efficiency was improved to 3.5% following the post-treatment of the cell with NaOH. We also proposed a simple mathematical model to explain the dependence of the efficiency on the amount of copper. Efficiencies of more than 3% for solar cells made by a simple method and using inexpensive materials make these solar cells promising competition for the current commercial solar cells. Graphical abstract: Current-Voltage characterization of solar cell with deposition of copper particles by PVEP for 30 s Highlights: The manufacture of solar cell using TiO2 as photon absorbers and cooper bridges inserted between TiO2 particles was reported. The effect of the pulse duty cycle to the solar cell performance was explored. A simple model of the dependence of efficiency on the amount of copper was proposed.